Positioning the National Health Insurance for financial sustainability and Universal Health Coverage in Ghana: A qualitative study among key stakeholders. - Moses Aikins (Public Library of Science (PLoS), 2021)
Introduction The National Health Insurance Scheme (NHIS) was introduced in 2003 to reduce "out-of-pocket" payments for health care in Ghana. Over a decade of its implementation, issues about the financial sustainability of this pro-poor policy remains a crippling fact despite its critical role to go towards Universal Health Coverage. We therefore conducted this study to elicit stakeholders' views on ways to improve the financial sustainability of the operations of NHIS. Methods Twenty (20) stakeholders were identified from Ministry of Health, Ghana Health Services, health workers groups, private medical practitioners, civil society organizations and developmental partners. They were interviewed using an interview guide developed from a NHIS policy review and analysis. All interviews were recorded and transcribed verbatim. The data were analysed thematically with the aid of NVivo 12 software. Results Stakeholders admitted that the NHIS is currently unable to meet its financial obligations. The stakeholders suggested first the adoption of capitation as a provider payment mechanism to minimize the risk of providers' fraud and protection from political interference. Secondly, they indicated that rapid releases of specific statutory deductions and taxes for NHIS providers could reduce delays in claims' reimbursement which is one of the main challenges faced by healthcare providers. Aligning the NHIS with the Community-based Health Planning and Services and including preventive and promotive health is necessary to position the Scheme for Universal Health Coverage. Conclusion The Scheme will potentially achieve UHC if protected from political interference to improve the governance and transparency that affects the finances of the scheme and the expansion of services to include preventive and promotive services and cancers.